Acoustics of the Blue Whale Auditorium in Buenos Aires. Issue 3 (September 2021) - Basso, Gustavo
The "Blue Whale" Auditorium in Buenos Aires opened in 2015. Designed to be the headquarters of the National Symphony Orchestra of Argentina, its goal was to become the city's main space for symphonic music. The architectural program posed several challenges from an acoustic point of view, as 2000 people had to be accommodated in a square space into which none of the usual architectural typologies fit properly. It was decided, therefore, to place in this space an "ad-hoc" hall. The design centered around three main premises: to achieve an enveloping acoustic field, to establish an adequate reverberation decay, and to combine reflective and diffusing surfaces to attain a similar acoustic field through the entire audience area. This work details the design process of the Auditorium, during which the final shape was deduced from the established acoustic premises, and some acoustical measurements made in the finished hall.